Polycaprolactone for Hard Tissue Regeneration: Scaffold Design and In Vivo Implications - Fernanda Ramírez-Ruiz; Israel Núñez-Tapia; María Cristina Piña-Barba; Marco Antonio Alvarez-Pérez; Vincenzo Guarino; Janeth Serrano-Bello (Bioengineering)
In the last thirty years, tissue engineering (TI) has emerged as an alternative method to regenerate tissues and organs and restore their function by implanting specific lineage cells, growth factors, or biomolecules functionalizing a matrix scaffold. Recently, several pathologies have led to bone loss or damage, such as malformations, bone resorption associated with benign or malignant tumors, periodontal disease, traumas, and others in which a discontinuity in tissue integrity is observed. Bone tissue is characterized by different stiffness, mechanical traction, and compression resistance as a function of the different compartments, which can influence susceptibility to injury or destruction. For this reason, research into repairing bone defects began several years ago to find a scaffold to improve bone regeneration. Different techniques can be used to manufacture 3D scaffolds for bone tissue regeneration based on optimizing reproducible scaffolds with a controlled hierarchical porous structure like the extracellular matrix of bone. Additionally, the scaffolds synthesized can facilitate the inclusion of bone or mesenchymal stem cells with growth factors that improve bone osteogenesis, recruiting new cells for the neighborhood to generate an optimal environment for tissue regeneration. In this review, current state-of-the-art scaffold manufacturing based on the use of polycaprolactone (PCL) as a biomaterial for bone tissue regeneration will be described by reporting relevant studies focusing on processing techniques, from traditional—i.e., freeze casting, thermally induced phase separation, gas foaming, solvent casting, and particle leaching—to more recent approaches, such as 3D additive manufacturing (i.e., 3D printing/bioprinting, electrofluid dynamics/electrospinning), as well as integrated techniques. As a function of the used technique, this work aims to offer a comprehensive overview of the benefits/limitations of PCL-based scaffolds in order to establish a relationship between scaffold composition, namely integration of other biomaterial phases’ structural properties (i.e., pore morphology and mechanical properties) and in vivo response.